The Effect of Flavonoid Fraction from Vitex trifolia Leaves on Pandemic-2009 H1N1 Influenza A Virus Propagated in Embryonated Chicken Eggs - Neny Purwitasari1 , Krisma Agung Subarka2 , David Fransnado Grismana Putra2 , Herra Studiawan3 , Kun (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this study is to investigate antiviral activity of flavonoid fraction of Vitex trifolia leaves towards influenza A viruses H1N1 pandemic-2009 that were propagated in embryonated chicken eggs (ECEs). Fraction that rich of flavonoid compounds was isolated from the crude ethanolic extract using column chromatography, prior to be subjected to antiviral inhibition assay. The assay was evaluated by using hemagglutination (HA) test. The HA titre reduction of the virus was counted after being treated with the flavonoid fraction, compared to untreated one. The result showed that percentage of inhibition of this flavonoid fraction against pandemic-2009 H1N1 influenza A virus are 37.50%, 71.25%, 71.25% at concentration 125 ?g/mL, 500 ?g/mL, and 750 ?g/mL, respectively. In conclusion, the flavonoid fraction of Vitex trifolia leaves showed effect to reduce viral hemaglutinine, the enzyme that has a crucial role in the initiating step of virus infection, without possesed any toxicity to ECEs.